5(4x-3)=10(2x+1)-25

3(x+2)-7(2-3x)=8(x-3)

(2x-3)/5=3/5-2x


Odpowiedź :

Odpowiedź:

5( 4x-3) = 10 ( 2x+1) -25

 20x -15 =   20x +10-25

     20x - 20 x =10-25 +15

   20x-20x = 25-25

           0=0

równanie  tożsamościowe

3( x+2) - 7 ( 2-3x)= 8(x-3)

   3x+6 - 14 +21 x = 8x -24

    3x +21 x -8x = -24 -6 +14

     16x= - 16 /:16

     x= - 1

spr...  3*(-1) +6 -14 +21*(-1)= 8*(-1) -24

          -3 +6 -14 -21 = -8 -24

           -38 + 6= -32

                - 32= - 32

                 L=P

( 2x-3)  /5=   3/5-2x   /*5

   2x-3 = 15/5 - 10x

2x+10x = 3 +3

         12x= 6 /:12

              x= 1/2

spr..   2*1/2 -3 = 3 -10*1/2

           1-3= 3 -5

          -2= - 2

             L=P

     

Szczegółowe wyjaśnienie:

Odpowiedź:

Szczegółowe wyjaśnienie:

5(4x-3)=10(2x+1)-25

20x-15=20x+10-25

20x-15=20x-15

0=0

3(x+2)-7(2-3x)=8(x-3)

3x+6-14+21x=8x-24

24x-8=8x-24

16x= -16/:16

x=-1

(2x-3)/5=3/5-2x

3(2x-3)=5(5-2x)

6x-9=25-10x

16x=34/:16

x=2 2/16=2 1/8